2016
DOI: 10.1160/th14-12-1050
|View full text |Cite
|
Sign up to set email alerts
|

Combined assessment of thrombotic and haemorrhagic risk in acute medical patients

Abstract: Acute medical patients have a high risk of venous thromboembolic events (VTE). Unfortunately, the fear of bleeding complications limits the use of antithrombotic prophylaxis in this setting. To stratify the VTE and haemorrhagic risk, two clinical scores (PADUA, IMPROVE) have recently been developed. However, it is not clear how many patients have a concomitant high VTE and haemorrhagic risk and what is the use of prophylaxis in this situation. To clarify these issues we performed a prospective cohort study enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
2
13
1
Order By: Relevance
“…Combining thrombotic and hemorrhagic risk assessments, pharmacological and nonpharmacological measures can be adopted to safely reduce in-hospital VTE [128].…”
Section: Prevention Of Venous Thromboembolismmentioning
confidence: 99%
“…Combining thrombotic and hemorrhagic risk assessments, pharmacological and nonpharmacological measures can be adopted to safely reduce in-hospital VTE [128].…”
Section: Prevention Of Venous Thromboembolismmentioning
confidence: 99%
“…In this context, The Padua Prediction Score (PPS) and the Improve Bleeding Score (IBS) have been approved by The American College of Chest Physicians 9 th Edition guidelines as validated tools for VTE risk assessment in hospitalized old medical patients 91 . Some data suggest that a positive PPS and IBS are associated with early mortality in Internal Medicine patients 92 , but it has been demonstrated, in a group of old hospitalized patients, that their additional predictive accuracy is modest (positive PPS sensitivity: 96.67%, specificity: 20.74%; IBS sensitivity: 20.88%, specificity: 90.45%), resulting not very useful in clinical practice 93 . Anyway, few studies about using these models in very old subjects are available.…”
Section: Thromboprophylaxis and Risk Of Bleeding In Older Populationmentioning
confidence: 99%
“…This suggests a positive relationship between the two risks, complicating the decision making. A recent evaluation of combined risk assessment concluded that the physicians' attitudes on prescribing prophylaxis was more influenced by VTE-than bleeding risk when evaluating patients with both high VTEand bleeding risk [34].…”
Section: Risk Assessment Comparisonmentioning
confidence: 99%